Analysis of Job Satisfaction Levels Among Islamic Religious Education Teachers in Kabupaten Agam - Nurul Mawaddah Al-Mursal; Zulfani Sesmiarni (Jurnal Bina Ilmu Cendekia, 2025)
This study aims to analyze the level of job satisfaction among Islamic Education (PAI) teachers in Agam Regency, West Sumatra, Indonesia. Employing a quantitative descriptive approach, data were collected through structured questionnaires administered to 138 PAI teachers across various educational levels. The descriptive analysis revealed a generally high level of job satisfaction, with 51.4% of respondents categorized as "Very Satisfied" and 43.5% as "Satisfied." The mean job satisfaction score reached 190.59 out of a maximum of 225, indicating that most teachers experience fulfillment across multiple dimensions, including work environment, leadership, rewards, and interpersonal relationships. These findings suggest that the majority of PAI teachers perceive their professional, emotional, and administrative needs as being adequately met. Nevertheless, a small proportion of respondents reported lower satisfaction levels, highlighting the need for further qualitative investigation. The results provide empirical insights that may inform educational policymakers and school management in formulating strategies to enhance teacher well-being, motivation, and professional performance within Islamic education contexts.